1985
DOI: 10.1139/v85-089
|View full text |Cite
|
Sign up to set email alerts
|

The photolysis and thermal decomposition of pyruvic acid in the gas phase

Abstract: The photolysis of pyruvic acid vapour has been studied at wavelengths of 366, 345, and 320 nm, at a temperature of 340 K and pressures from about I to 10 Torr. Products observed were COZ and CH3CH0, with the former always in excess, and a quantum yield of COr of 0.9 ? 0. I at 366 nm. Light emission was also observed, and from the effect of added 0, it was concluded that emission occurred from both singlet and triplet states. It is suggested that the primary process in the photolysis is an internal hydrogen-ato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
124
1

Year Published

1985
1985
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(137 citation statements)
references
References 8 publications
12
124
1
Order By: Relevance
“…Assuming these calculations to be at least qualitatively correct, it seems likely that the UV photochemistry of PA with light of λ > 300 nm proceeds according to the sequence S 0 → S 1 → T 2 → T 1 . This intersystem crossing to the triplet surface is markedly different from the gas phase photochemistry, which occurs solely on the singlet surface to generate methylhydroxycarbene (28)(29)(30)54). However, in the aqueous study presented here, PA is seen to react from its T 1 state to produce acetoin, lactic and acetic acids, and oligomers, as described below and depicted in Scheme 1.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Assuming these calculations to be at least qualitatively correct, it seems likely that the UV photochemistry of PA with light of λ > 300 nm proceeds according to the sequence S 0 → S 1 → T 2 → T 1 . This intersystem crossing to the triplet surface is markedly different from the gas phase photochemistry, which occurs solely on the singlet surface to generate methylhydroxycarbene (28)(29)(30)54). However, in the aqueous study presented here, PA is seen to react from its T 1 state to produce acetoin, lactic and acetic acids, and oligomers, as described below and depicted in Scheme 1.…”
Section: Discussionmentioning
confidence: 69%
“…PA undergoes decarboxylation in the gas and aqueous phases by means of different mechanisms. Decarboxylation of gas phase PA has been seen to occur thermochemically, through IR multiphoton pyrolysis, as well as through UV and visible excitation (13,(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36). The main removal pathway of gas phase PA from the troposphere is UV photolysis, with reaction with OH radical providing a minor contribution (31).…”
mentioning
confidence: 99%
“…Fig. 3 shows also the spectra reported previously by Yamamoto and Back [10] and very recently by Horowitz et al [11]. Yamamoto and Back reported only the relative absorption spectrum at 358 K which was normalized by Horowitz et al by using the value of the cross-section at 350 nm (σ = 3.82 × 10 −20 cm 2 molecule −1 ) quoted by Berges and Warneck [12].…”
Section: Uv Absorption Spectramentioning
confidence: 67%
“…The photolysis of pyruvic acid has been studied by different groups using a variety of conditions and light sources. Yamamoto and Back [10] used a Hg-Xe high-pressure arc lamp to study the photolysis of PA at 366, 345 and 320 nm while Berges and Warneck [12] used a xenon arc lamp centered at 350 nm. Both studies showed that acetaldehyde and CO 2 were the major products confirming what was reported earlier by Vesley and Leermakers at 366 nm [16].…”
Section: Photodissociation Of Pa Using Black Lampsmentioning
confidence: 99%
“…It is an interesting example of an a-dicarbonyl compound locked into the usually less stable cis configuration; it is also of interest in relation to other cyclic ketones, especially cyclobutanone. Both cyclobutanone (2) and several simple a-dicarbonyl compounds (3)(4)(5)(6) have been the subjects of recent research in this laboratory, and for comparison with these systems we have undertaken studies of the spectroscopy, photochemistry, and thermal decomposition of CBD in the vapor phase. The present paper describes the thermal decomposition.…”
Section: Introductionmentioning
confidence: 99%